Public Education in Brazil: an incomplete democratization: Educação Pública no Brasil: a democratização inconclusa - Dias Navarro Barreto, Raylane Andreza; de Souza Chaloba, Rosa Fátima (Araucaria, 2022)
As a way of thinking the Brazilian education in the ephemeris of Brazil's 200 years of independence, we have selected as an object of analysis the trajectory of public education in Brazil since the expansion of its school system. Inspiring in the historical research method from documentary and bibliographical research and sources as laws, decrees and statistical data, the article was divided in two parts: The first part concerns to the Brazilian public education irresolute pathways, after its announced political independence from the Portuguese kingdom. Then, the second part concerns to the basic education dissemination long trajectory conquest in the 20th century. The result makes us question the future of public education in the face of the elections in the emblematic year of 2022.